PENERAPAN MOTION TWEEN UNTUK ANIMASI DUA DIMENSI RUTE PERJALANAN BUS TRANS JOGJA - Nugrahenny, Dwi; Honggowibowo, Anton Setiawan; Mukti, Mega Lesya (SENATIK STT Adisutjipto, 2013)
TransportationÂ  isÂ  oneÂ  ofÂ  theÂ  importantÂ  aspectsÂ  inÂ  aÂ  region,Â  whereÂ  public transportationÂ  takeÂ  effectÂ  onÂ  theÂ  mobilityÂ  ofÂ  theÂ  people.Â  ToÂ  achieveÂ  aÂ  good transportation can be create, so that the infrastructure and other supporting factors areÂ  needed. Yogyakarta municipalityÂ  areaÂ  hasÂ  a lotÂ  ofÂ  public transportasion,Â  oneÂ  of themÂ  isÂ  â€œTransÂ  Jogjaâ€Â  bus,Â  whereÂ  eachÂ  busÂ  lineÂ  hasÂ  itsÂ  routeÂ  toÂ  reachÂ  any destination.Â  ItÂ  isÂ  neededÂ  aÂ  supportingÂ  mediaÂ  thatÂ  canÂ  provideÂ  informationÂ  aboutÂ  the route for each bus line so that people can be easily deciding which bus line that can use to reach their destination. Those information presented in the form of animation withÂ  anÂ  interestingÂ  andÂ  informativeÂ  media.Â  TheÂ  useÂ  ofÂ  animationÂ  asÂ  anÂ  information mediaÂ  thatÂ  shownÂ  asÂ  aÂ  routeÂ  trip,Â  busÂ  lineÂ  includingÂ  busÂ  stopÂ  andÂ  departing passangersÂ  placeÂ  assessedÂ  canÂ  beÂ  useÂ  asÂ  oneÂ  ofÂ  theÂ  otherÂ  optionÂ  forÂ  obtaining information except from a conventional map.